A strategic model to enhance the competitiveness of halal MSMEs through halal certification, digital marketing, and creative branding - Bakti, Surya; Syarifah, Tengku; Alawiyah, Nurul Hikmatul; Syahputa, M. Sandi; Mutia, Dea; Sariani, Sariani (Journal of Economics and Business Letters, 2025)
This community service program was conducted to enhance the competitiveness of halal MSMEs in Binjai Baru Village, Datuk Tanah Datar District, Batu Bara Regency, North Sumatera Province, Indonesia, through three key interventions: halal certification awareness, digital marketing training, and creative branding workshops. The primary issues faced by MSMEs in this area include a limited understanding of halal certification procedures, low utilization of digital platforms for promotion, and weak brand identity, which affects product attractiveness. The program’s implementation method consisted of preparation, execution, and evaluation stages involving field observation, awareness sessions, hands-on digital marketing practice, and branding assistance. The results indicate a significant improvement in the participants’ understanding of the benefits of halal certification, their ability to use social media for product promotion, and their initial skills in designing brand identities and product packaging. The participants demonstrated high enthusiasm and were able to gradually apply the materials provided. Overall, this program successfully strengthened the legal, digital marketing, and branding capacities of local MSMEs, forming a solid foundation for enhancing sustainable competitiveness in the halal industry.